China's energy intensity target allocation needs improvement! Lessons from the convergence analysis of energy intensity across Chinese Provinces. (20th June 2019) - Zhang, Pan; Wang, Xiao; Zhang, Nan; Wang, Yiyang
Abstract: To explore the reasonability of the decomposition of China's national energy intensity target, we tested the convergence of energy intensity across 30 Chinese provinces, including stochastic convergence, β-convergence, and ó-convergence. Based on panel data from 30 Chinese provinces across three Five-Year Plan periods, the results confirmed the existence of stochastic convergence and β-convergence, but did not prove the existence of ó-convergence in China's energy intensity. In addition, by comparing the convergence speed over the three Five-Year Plan periods, the results showed that China's energy intensity targets for the provinces slowed β-convergence in energy intensity during the 11th and 12th Five-Year Plan periods, highlighting the need to optimize the decomposition of China's national energy intensity target. Finally, issues related to the decomposition of China's national energy intensity target were discussed and policy suggestions were proposed to optimize it from the perspective of promoting the convergence of energy intensity across Chinese provinces. Highlights: Stochastic convergence, β-convergence, and ó-convergence of energy intensity were tested in three Five-Year Plan periods. Stochastic convergence and β-convergence of energy intensity across Chinese provinces existed, but ó-convergence didn't. China's energy intensity targets for the provinces slowed β-convergence in the 11th and 12th Five-Year Plan periods.